1999
DOI: 10.1126/science.286.5449.2528
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous Germ Line hCHK2 Mutations in Li-Fraumeni Syndrome

Abstract: The hCHK2 gene encodes the human homolog of the yeast Cds1 and Rad53 G2 checkpoint kinases, whose activation in response to DNA damage prevents cellular entry into mitosis. Here, it is shown that heterozygous germ line mutations in hCHK2 occur in Li-Fraumeni syndrome, a highly penetrant familial cancer phenotype usually associated with inherited mutations in the TP53 gene. These observations suggest that hCHK2 is a tumor suppressor gene conferring predisposition to sarcoma, breast cancer, and brain tumors, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
612
5
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 836 publications
(646 citation statements)
references
References 52 publications
18
612
5
5
Order By: Relevance
“…Two of the variants, a missense variant 470T4C (I157T) in exon 3 and a frameshift mutation 1100delC in exon 10, were the same as previously reported in patients with Li -Fraumeni syndrome (Bell et al, 1999), breast (Allinen et al, 2001;Vahteristo et al, 2002), and prostate cancer (Dong et al, 2003). The frameshift 1100delC mutation has been proven to result in the loss of kinase activity (Wu et al, 2001), and I157T variant has been shown to be defective in its ability to bind and phosphorylate Cdc25A, one of its normal substrates (Falck et al, 2001).…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…Two of the variants, a missense variant 470T4C (I157T) in exon 3 and a frameshift mutation 1100delC in exon 10, were the same as previously reported in patients with Li -Fraumeni syndrome (Bell et al, 1999), breast (Allinen et al, 2001;Vahteristo et al, 2002), and prostate cancer (Dong et al, 2003). The frameshift 1100delC mutation has been proven to result in the loss of kinase activity (Wu et al, 2001), and I157T variant has been shown to be defective in its ability to bind and phosphorylate Cdc25A, one of its normal substrates (Falck et al, 2001).…”
Section: Resultssupporting
confidence: 61%
“…These variants were further studied in a set of 1137 samples. In addition, a silent exonic change also reported by Bell et al (1999), an intronic change (not affecting splice site), and a novel missense mutation 1312G4T (D438Y) were observed. D438Y mutation was found only in one proband.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Specifically, germ-line mutations in Chk2 are thought to act as low-penetrance predisposition alleles in breast and possibly other cancer types (Nevanlinna and Bartek, 2006), and in a small subset of Li-Fraumeni or Li-Fraumeni-like syndrome kindreds (Bell et al, 1999). In addition, somatic mutations affecting Chk2 occur sporadically at low frequency in various human tumour types (Miller et al, 2002).…”
Section: Introductionmentioning
confidence: 99%